A masterclass in contrarian writing - Reviewed by C.P. Surendran (BIBLIO: A Review of Books)
Why the poor don$1 (Bt kill us: The psychology of Indians, by Manu Joseph, Aleph book company, New Delhi 2025, 266pp. Rs.599 (HB) ISBN 9789365234572. Reproduced s